Chronic exposure to ambient particulate matter induces gut microbial dysbiosis in a rat COPD model - Li, Naijian (Respir Res, 2020)
BACKGROUND: The role of the microbiota in the pathogenesis of chronic obstructive pulmonary disease (COPD) following exposure to ambient particulate matter (PM) is largely unknown. METHODS: Fifty-four male Sprague-Dawley rats were exposed to clean air, biomass fuel (BMF), or motor vehicle exhaust (MVE) for 4, 12, and 24 weeks. We performed pulmonary inflammation evaluation, morphometric measurements, and lung function analysis in rat lung at three different times points during exposure. Lung and gut microbial composition was assessed by 16S rRNA pyrosequencing. Serum lipopolysaccharide levels were measured and short-chain fatty acids in colon contents were quantified. RESULTS: After a 24-week PM exposure, rats exhibited pulmonary inflammation and pathological changes characteristic of COPD. The control and PM exposure (BMF and MVE) groups showed similar microbial diversity and composition in rat lung. However, the gut microbiota after 24 weeks PM exposure was characterized by decreased microbial richness and diversity, distinct overall microbial composition, lower levels of short-chain fatty acids, and higher serum lipopolysaccharide. CONCLUSION: Chronic exposure to ambient particulate matter induces gut microbial dysbiosis and metabolite shifts in a rat model of chronic obstructive pulmonary disease.